La fabrication de l'élève en difficulté - Christophe Roiné
This paper reexamines a study conducted in 2009 regarding pupils with special education needs. Our leading question is : How did Pierre Bourdieu's work sustain this research, as much in terms of epistemological stance as methodological direction ? Pierre Bourdieu's work is fertile in developing an analytical and critical point of view on a research object. Our discussion focuses on Bourdieu's "a-substantialist assumption" and notion "practical logic" to show their heuristic power in research. These premises allow us to question the concept of "category" (of pupils).